Preliminary investigation of the in vitro anti-Helicobacter pylori activity of Triphala - Zhixiang Zhu; Yuanjing Zou; Ling Ou; Meiyun Chen; Yujiang Pang; Hui Li; Yajie Hao; Bingmei Su; Yuqian Lai; Liping Zhang; Junwei Jia; Ruixia Wei; et al. (Frontiers Media S.A., 2024)
BackgroundTriphala, is a composite of three individual botanical drugs: Terminalia chebula, Terminalia bellirica, and Emblica officinalis. It exhibits properties such as heatclearing, anti-inflammatory, anti-fatigue, antioxidant, and antibacterial effects,making it extensively utilized in India and Tibet. It has been found to exhibitinhibitory effects on Helicobacter pylori (H. pylori); however, further comprehensive research is still needed to elucidate its specific antibacterial mechanism. The present study investigates the in vitro antibacterial activity and antibacterial mechanism of Triphala against H. pylori.MethodsOurs research investigates the in vitro inhibitory activity of Triphala on multiple standard and clinical strains using microdilution broth method, time-kill curve, time-bactericidal curve and scanning electron microscopy (SEM). Furthermore, the antibacterial mechanism of Triphala is further explored through experiments on urease activity, biofilm formation, anti-adhesion properties, virulence actor assays using RT-qPCR and Western Blotting techniques.ResultsThe research findings indicate that Triphala exhibits a minimum inhibitory concentration of 80-320 μg/mL against both standard and clinical strains of H. pylori. Triphala exerts its anti-H. pylori effect by perturbing the microstructure of H. pylori, downregulating adhesion-associated genes (alpA, alpB, babA), urease-related genes (ureA, ureB, ureE, ureF), and flagellar genes (flaA, flaB); inhibiting bacterial adhesion, biofilm formation, urease activity as well as CagA protein expression.DiscussionThese findings suggest that Triphala exerts inhibitory effects on H. pylori activity through multiple mechanisms, underscoring its potential as a new drug for the prevention and treatment of H. pylori infection.